KONSEPSI PENCEGAHAN BAHAYA NARKOBA SERTA KONSEKUENSI BAGI PENGGUNA DAN PENGEDAR DALAM PERSPEKTIF HUKUM DI DESA ALASSUMUR LOR KEC. BESUK PROBOLINGGO - Rizal, Sofian Syaiful; Irsyan, Muh (Universitas Nurul Jadid, 2022)
It is undeniable that there are still many who consume drugs in the environment around us. The impact on health and the future is not small. The dangers of drugs for addicts and young people, students are very many and if the habit of consuming drugs is not immediately stopped then this will worsen the health status of the users themselves slowly but surely and will damage the future of their lives. students need a conducive and comfortable environment from drug abuse, therefore drug control is a shared responsibility starting from the family, then the community and the government. Through this service activity, it is expected to be able to provide an understanding to the community in Karo Regency about the dangers suffered by drug abuse, types and types of narcotics and how to overcome them. The method used is qualitative with direct interviews with the person concerned and provides socialization of the correct understanding of the effects of drugs as well as a question and answer discussion about types of drugs, their dangers and effective steps so that the community in Alassumur Lor village kec. Tomorrow we can tackle it early and work together to tackle drugs together with family, then community and government.Keywords: Consequences, Drugs and Legal Perspective